Argumentações e construção da aprendizagem segundo docentes de ciências: um panorama no contexto do ensino de ciências da rede pública da cidade de Codó/MA - PEREIRA, Elrilene da Cruz (2023)
This research aims to investigate and understand the different approaches and techniques used by teachers in the educational context, with the purpose of encouraging the development of students' argumentation skills in science classes from 6th to 9th grade in the public education system in the city of Codó-Maranhão, during the process of scientific education, in order to comprehend the dynamics of learning through the teaching strategies used in the classroom. The research addresses the importance of arguments as a pedagogical tool to promote critical thinking and the development of scientific knowledge. Thus, the study was based on a qualitative approach, using semi-structured interviews with science teachers working in the final years of elementary education. For data analysis, content analysis was used, in which we extracted Units of Meaning and grouped them into a systemic network with their categories and subcategories, through a careful analysis of the collected data, the main strategies used by teachers to promote argumentation in the classroom were identified. The results also revealed that arguments play a fundamental role in the construction of students' scientific knowledge. By being encouraged to express their ideas, formulate hypotheses, and debate concepts, students develop essential cognitive skills, as well as learn to communicate their opinions clearly and based on evidence. However, the research also pointed out challenges faced by teachers in the effective implementation of argumentation in science education. Among them, the lack of specific training to deal with this approach, the limitation of didactic resources, and the need for institutional support to improve pedagogical practice stand out. Considering these results, this study advocates the importance of investing in continuous training for teachers, providing adequate resources, and creating institutional spaces for discussion and exchange of experiences. Thus, it will be possible to strengthen the use of arguments as a pedagogical strategy and, consequently, improve the quality of science education in the public education system of Codó/MA.